On the Guard of World Peace. Scientific and Research Organizations in NATO Structures 1952-2022. Problem Outline (Global Journal of Science Frontier Research, 2024)
Scientific research organizations have a long-standing tradition in NATO's history, testifying to the great role that Alliance decision-makers attach to scientific research. Thanks to comprehensive scientific development, the existence of specialized scientific institutions and cooperation with research units of member states, it was and is possible to develop and grow NATO's power. Thanks to scientists, the Alliance has for many years been a world leader in the development and application of modern military technology. The assembly and cooperation of leading representatives of the scientific and technological world of the member countries has made it possible to develop and implement many innovations in the field of defence. With the passage of years, it has become necessary to develop specialized scientific and research institutions, conducting new research and addressing further challenges facing the defence policy of the Alliance.
Keywords: NATO; science; AGARD; DRG; RTO; STO; SPS; SACLANTCEN; NURC; CMRE